Microevolution and independent incursions as main forces shaping H5 Hemagglutinin diversity during a H5N8/H5N5 highly pathogenic avian influenza outbreak in Czech Republic in 2017 - Křivda, Vlastimil; Dán, Ádám; Černíková, Lenka; Vitásková, Eliška; Křivda, Vlastimil; Horníčková, Jitka; Masopust, Roman; Sedlák, Kamil (Archives of virology, 2018)
Here, we present a comprehensive analysis of the H5N8/H5N5 highly pathogenic avian influenza (HPAI) virus strains detected in the Czech Republic during an outbreak in 2017. Network analysis of the H5 Hemagglutinin (HA) from 99% of the outbreak localities suggested that the diversity of the Czech H5N8/H5N5 viruses was influenced by two basic forces: local microevolution and independent incursions. The geographical occurrence of the central node H5 HA sequences revealed three eco-regions, which apparently played an important role in the origin and further spread of the local H5N8/HPAI variants across the country. A plausible explanation for the observed pattern of diversity is also provided.
Keywords: Virulence; Animals; Birds; ptačí chřipka u ptáků; Evolution, Molecular; hemaglutininové glykoproteiny viru chřipky; molekulární evoluce; Hemagglutinin Glycoproteins, Influenza Virus; ptáci; virus chřipky A; Genetic Variation; Influenza A virus; virulence; virus chřipky A, podtyp H5N8; Phylogeny; Disease Outbreaks; Czech Republic; Influenza A Virus, H5N8 Subtype; Influenza in Birds; Česká republika; epidemický výskyt choroby; zvířata; fylogeneze; genetická variace